2007
DOI: 10.1080/09638230701279865
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and employment: An overview of patterns and policies across Western Europe

Abstract: Background: The relationship between mental health problems and employment is receiving growing attention across Europe as the cost of lost productivity is appreciated. Aims: This paper reports on the preliminary collection of data on employment of people with mental health problems and related economic issues in 17 countries participating in the Mental Health Economics European Network (MHEEN). Method: A questionnaire was developed with the Network partners and statistical and narrative data collected. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…The supervisors expressed concerns that the social security system or other stakeholders might push someone into a job. The Individual Placement and Support model (IPS) emphasizes that trainees have to want the job themselves [33,65]. It was evident that the supervisors in the present study respect their trainees, believe in their abilities and capacity, and emphasize the healthy aspects of their work.…”
Section: Substantive Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The supervisors expressed concerns that the social security system or other stakeholders might push someone into a job. The Individual Placement and Support model (IPS) emphasizes that trainees have to want the job themselves [33,65]. It was evident that the supervisors in the present study respect their trainees, believe in their abilities and capacity, and emphasize the healthy aspects of their work.…”
Section: Substantive Discussionmentioning
confidence: 68%
“…The standard work rehabilitation approach for those with mental health issues has evolved from the "train then place" model of the 1970s to today's "place then train" paradigm, based on early placement in a competitive job [30][31][32][33][34][35]. Depending on whether the trainee has a job history; job placement may take the form of job-entry or a return-to-work approach, either of which would involve occupational habilitation or rehabilitation processes [36].…”
mentioning
confidence: 99%
“…Indeed, it has been reported that the impact of unemployment and other adverse circumstances on health in times of crisis can be evident only after many years, especially in disadvantaged populations [34]. It is also very important to have a sufficient time-perspective prior to the beginning of the crisis in order to assess whether the crisis itself has had an added effect on trends that were already occurring.…”
Section: Why Are These Results Observed? Reflections On the Effect Ofmentioning
confidence: 99%
“…It accounts for almost 12% of total years lived with disability in the world (Ustun and Chatterji, 2001) (World Health Organization, 2008), and represents the first cause of premature retirement and absence from work due to illness in many European countries (Curran et al, 2007). Furthermore it is the most costly brain disorder in the continent, accounting for 33% of their total cost (Sobocki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%